Combination of FDG-PET and UCSF Criteria for Predicting HCC Recurrence After Living Donor Liver Transplantation. Issue 9 (September 2016) - Hsu, Chien-Chin; Chen, Chao-Long; Wang, Chih-Chi; Lin, Chih-Che; Yong, Chee-Chien; Wang, Shih-Ho; Liu, Yueh-Wei; Lin, Ting-Lung; Lee, Wei-Feng; Lin, Yu-Hung; Chan, Yi-Chia; Wu, Yi-Ju; et al.
Abstract : Background: F-18 fluorodeoxyglucose (FDG) uptake in hepatocellular carcinoma (HCC) is related to tumor biology and has predictive value for tumor recurrence after liver transplantation. This retrospective study assessed whether the degree of FDG uptake in positron emission tomography (PET) can be used to predict HCC recurrence after living donor liver transplantation (LDLT). Methods: One hundred forty-seven patients with HCC underwent FDG-PET studies before LDLT. The semiquantification of FDG uptake in FDG-positive HCC was done with maximum standardized uptake value (SUVmax ) and tumor to nontumor ratio (TNR). Recurrence-free survivals (RFS) were calculated using the Kaplan-Meier method. Results: In univariable analysis, T stage, presence of microvascular invasion, being FDG-positive, SUVmax, and TNR were significant predictors for worse RFS. The optimal cutoff values of SUVmax and TNR were 4.8 and 2.0, respectively. The high FDG uptake HCC (TNR ≥ 2) was a strong predictor for worse RFS (hazard ratio, 13.52; 95% confidence interval, 4.77-38.29; P < 0.001). Using a combination of FDG-PET and University of California San Francisco (UCSF) criteria, the patients can be divided into low-risk (within UCSF criteria and FDG-negative), intermediate-risk (beyond UCSF criteria and FDG-negative; FDG-positive and TNR < 2), and high-risk (FDG-positive and TNR ≥ 2) groups. The estimated 5-year RFS in these groups were 85.5%, 83.9%, and 29.6% according to the combination of FDG-PET and clinical UCSF criteria, and 94.0%, 75.8%, and 29.6% according to the combination of FDG-PET and pathologic UCSF criteria, respectively. Conclusions: Combination of FDG-PET and UCSF criteria can be used to predict the risk of HCC recurrence after LDLT. Abstract : HCC recurrence after liver transplantation is still a significant problem despite efforts to minimize this complication by a careful selection process mainly based on morphologic criteria. The authors show an association between FDG-PET (positivity as well as semiquantification of FDG uptake), indirect marker of HCC grade and aggressive biological properties, with the risk of HCC recurrence, thereby enhancing the predictability of UCSF criteria after LDLT.